2020
DOI: 10.3390/cancers12061503
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Overcoming Mechanisms of PARP Inhibitor Resistance in Homologous Recombination Repair-Deficient and Repair-Proficient High Grade Serous Ovarian Cancer Cells

Abstract: High grade serous ovarian cancer (HGSOC) is a major cause of female cancer mortality. The approval of poly (ADP-ribose) polymerase (PARP) inhibitors for clinical use has greatly improved treatment options for patients with homologous recombination repair (HRR)-deficient HGSOC, although the development of PARP inhibitor resistance in some patients is revealing limitations to outcome. A proportion of patients with HRR-proficient cancers also benefit from PARP inhibitor therapy. Our aim is to compare mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Loss of PARG in BRCA2-deficient cells that are being treated with a PARPi is thought to lead to partial restoration of PARylation so that there is decreased PARP trapping and also some return of DNA-damage repair signaling, ultimately leading to PARPi resistance [123] . Studies conducted to assess mechanisms of resistance to PARPi in ovarian cancer cells detected reduced PARG levels in both HR-proficient and HR-deficient cell lines [124] , supporting the notion that loss of PARG can contribute to the development of PARPi drug resistance. Interestingly, in cells that have not been previously treated with PARPi, inhibition of PARG appears to be synthetically lethal with HR deficiency [125] , restoring PARPi sensitivity.…”
Section: Molecular Basis Of Drug Resistancementioning
confidence: 56%
See 1 more Smart Citation
“…Loss of PARG in BRCA2-deficient cells that are being treated with a PARPi is thought to lead to partial restoration of PARylation so that there is decreased PARP trapping and also some return of DNA-damage repair signaling, ultimately leading to PARPi resistance [123] . Studies conducted to assess mechanisms of resistance to PARPi in ovarian cancer cells detected reduced PARG levels in both HR-proficient and HR-deficient cell lines [124] , supporting the notion that loss of PARG can contribute to the development of PARPi drug resistance. Interestingly, in cells that have not been previously treated with PARPi, inhibition of PARG appears to be synthetically lethal with HR deficiency [125] , restoring PARPi sensitivity.…”
Section: Molecular Basis Of Drug Resistancementioning
confidence: 56%
“…WEE1 kinase functions to prolong the G2 phase of the cell cycle by phosphorylating CDK1, thus inhibiting it and preventing it from initiating progression of the cell cycle while cells repair DNA damages. One study showed that both HR-deficient and HR-proficient high-grade serous ovarian cancer cells with resistance to olaparib were sensitive to treatment with WEE1 kinase inhibitor, AZD1775 [124] . It is thought that WEE1 inhibitors promote more DNA damage and thus cell death in the absence of inhibitor CDK1 phosphorylation.…”
Section: Therapeutic Options For Aquired Drug Resistancementioning
confidence: 99%
“…PARP inhibitors are now used as a maintenance therapy for patients with BRCA MUT epithelial ovarian cancer and as a treatment of relapsed BRCA MUT ovarian cancer in patients who have been treated with two or more chemotherapies before [ 32 , 33 ]. Despite their effectiveness, resistance to PARP inhibitors has been clinically reported [ 34 , 35 , 36 ]. Thus, it is critical to determine the mechanism of action of PARPi, as well as other inhibitors that compromise genomic stability linked to cell cycle disruption.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In high-grade serous ovarian carcinomas, some authors have suggested that one of the PARP inhibitor resistance mechanisms may be reduction in levels of poly(ADP-ribose) glycohydrolase (PARG), which would be expected to preserve a residual PARP1-initiated DNA damage response to DNA single-strand breaks. 17 Whether similar mechanisms of resistance are in action in the setting of PARP inhibition for PALB2-mutated cancers requires further investigation. Understanding the mechanisms of resistance will also help to inform the utility, if any, of switching between PARP inhibitors at progression, an issue for which there are currently limited data.…”
Section: Discussionmentioning
confidence: 99%